K-essence in the DGP brane-world cosmology - Bouhmadi-López, Mariam (2010)
We analyze a Dvali-Gabadadze-Porrati (DGP) brane filled with a k-essence field and assume the k field evolving linearly with the cosmic time of the brane. We then solve analytically the Friedmann equation and deduce the different behavior of the brane at the low- and the high-energy regimes. The asymptotic behavior can be quite different involving accelerating branes, big bangs, big crunches, big rips, or quiescent singularities. The latter correspond to a type of sudden singularity. © 2010 The American Physical Society.